2009
DOI: 10.1038/tpj.2009.59
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms of the cannabinoid receptor (CNR1) and fatty acid amide hydrolase (FAAH) genes with heroin addiction: impact of long repeats of CNR1

Abstract: Alterations in expression of a cannabinoid receptor (CNR1, CB1), and of fatty acid amide hydrolase (FAAH) that degrades endogenous ligands of CB1, may contribute to the development of addiction. The 385C>A in the FAAH gene and six polymorphisms of CNR1 were genotyped in former heroin addicts and control subjects (247 Caucasians, 161 Hispanics, 179 African Americans and 19 Asians). In Caucasians, long repeats (≥14) of 18087–18131 (TAA)8–17 were associated with heroin addiction (P = 0.0102). Across three ethnici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 45 publications
0
40
1
Order By: Relevance
“…In particular, no association between FAAH 385 genotype and alcoholism (Iwasaki et al, 2007) or methamphetamine dependence (Morita et al, 2005) were found in a study of Japanese. No association of FAAH 385 genotype with heroin addiction was found in an ethnically mixed sample (Proudnikov et al, 2010). Therefore, drug-specific studies have not replicated the observations made in polydrug abusers.…”
Section: 0 Associations Between Heterogeneity In Endocannabinoid Cmentioning
confidence: 87%
See 1 more Smart Citation
“…In particular, no association between FAAH 385 genotype and alcoholism (Iwasaki et al, 2007) or methamphetamine dependence (Morita et al, 2005) were found in a study of Japanese. No association of FAAH 385 genotype with heroin addiction was found in an ethnically mixed sample (Proudnikov et al, 2010). Therefore, drug-specific studies have not replicated the observations made in polydrug abusers.…”
Section: 0 Associations Between Heterogeneity In Endocannabinoid Cmentioning
confidence: 87%
“…Risk was associated with having at least 16 repeats and the effect size was small (odds ratio 1.55). In a study not included in the meta-analysis, AAT repeats of 14 or greater were significantly associated with heroin abuse in Caucasians as was the SNP at rs1049353 (Proudnikov et al, 2010). …”
Section: 0 Associations Between Heterogeneity In Endocannabinoid Cmentioning
confidence: 99%
“…This discovery may have important therapeutic implications. Indeed, even though globally active FAAH inhibitors exert few side effects in animals, human genetic studies suggest that long-term impairment of brain FAAH activity may result in increased vulnerability to substance abuse [35, 36]. Peripherally restricted FAAH inhibitors such as URB937 would not be subject to this potential risk.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have not detected an association between rs324420 and SU (Haughey et al, 2008; Proudnikov et al, 2010; Verweij et al, 2012), particularly in Asian populations (Iwasaki et al, 2007; Morita et al, 2005), the literature overwhelmingly supports a role for rs324420 in SU (Buhler et al, 2014; Flanagan et al, 2006). While one study found that subjects homozygous for the minor allele were 0.25 times less likely to be cannabis dependent (Tyndale et al, 2007), our results suggesting the A allele increases risk for CUDs are in line with previous findings (Li et al, 2011; Sipe et al, 2002).…”
Section: Discussionmentioning
confidence: 99%